Results of the clinical study «Hummingbird»: positive experience of import substitution in the treatment of osteoarthritis - S. K. Chechilova (Лечащий Врач)
Within the II All-Russian Scientific and practical conference ”Musculoskeletal pain in rheumatic diseases”, held in Moscow, on September 16, a satellite symposium «Results of the clinical study ”Hummingbird”: positive experience of import substitution in the treatment of osteoarthritis”. Osteoarthritis is among the TOP 10 disea es that cause disability in older people. The incidence of osteoarthritis has been increasing in recent years and represents a rather large socio-economic burden for society, because the need for expensive operations for endoprosthetics of large joints is increasing. The problem of pain in osteoarthritis and its chronization forces specialists to look for new approaches to the treatment of the disease. According to the presented data, the Russian innovative drug, developed in the order of import substitution, significantly reduces the pain syndrome and improves the functional state of the joints in most patients with osteoarthritis. It reduces the need for non-steroidal anti-inflammatory drugs and reduces their use by an average of two times. The drug has a fairly rapid effect – after the first course, a good result is visible. Ultrasound proves the anti-inflammatory effect of the drug.